Hybrid Approach for Channel Estimation Using Iterative Compensation and LMS Algorithm - Partap, Bhanu; Singh, Prabhjot; ., . (International Journal of Engineering and Technology, 2018)
In Orthogonal Frequency Division Multiplexing, the concept of channel equalization and estimation plays a vital role to improve the performance of the system by reducing the effects of distortion in the signals that occurs due to fading, multipath, delay spreads. In this study a hybrid channel estimation technique is developed by collaborating the iterative compensation mechanism with Least Mean Square technique. The performance of the proposed work is observed to be more effective and efficient than the Iterative compensation based channel estimation technique in the terms of Mean Square Error (MSE).Â Â